Erythropoietin acts as an anti-inflammatory signal on murine mast cells - Wiedenmann, Tanja; Erhardt, Stefanie; Cerny, Daniela; Hildebrand, Dagmar; Klein, Sabrina; Heeg, Klaus; Hieke-Kubatzky, Katharina (Molecular immunology, 2015)
Recently it was found that the erythropoietin receptor (EpoR) is expressed on innate immune cells, such as dendritic cells and macrophages. We found that murine bone marrow-derived mast cells express the EpoR and that its expression is increased under hypoxic conditions. Interestingly, Epo stimulation of the cells did not activate signal transducer and activator of transcription molecules, nor did we find differences in the expression of typical STAT-dependent genes, the proliferation rate, and the ability to differentiate or to protect the cells from apoptosis. Instead, we demonstrate that stimulation of mast cells with Epo leads to phosphorylation of the receptor tyrosine kinase c-kit. We hypothesize that this is due to the formation of a receptor complex between the EpoR and c-kit. The common beta chain of the IL-3 receptor family, which was described as part of the tissue protective receptor (TPR) on other non-erythroid cells, however is not activated. To investigate whether the EpoR/c-kit complex has tissue protective properties, cells were treated with the Toll-like receptor ligand LPS. Combined Epo and LPS treatment downregulated the inflammatory response of the cells as detected by a decrease in IL-6 and TNF-α secretion.